PENGARUH RETURN ON ASSETS, CURRENT RATIO, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Tantyazhari Utami; Dicky Arisudhana (CV. Denasya Smart Publisher, 2025)
This study investigates the influence of Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) on the stock prices of non-cyclical food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Using a purposive sampling method on 51 companies, this research analyzed 204 observational data through multiple linear regression. The results indicate that CR and EPS have a significant positive impact on stock prices, while DER has a significant negative impact. Conversely, ROA was found to have no significant effect. These findings suggest that during the post-pandemic economic recovery, investors in this defensive sector prioritized corporate liquidity, a healthy capital structure, and direct shareholder returns over asset utilization efficiency when making investment decisions.